Transforming Economics Learning in Phase E at Inclusive Senior High Schools: Developing the EcoLearn Application Based on M-Learning - Mufida, Amatulloh; Hakim, Luqman; Surjanti, Jun (IKIP PGRI Bojonegoro, 2025)
The learning process should encourage students’ initiative, creativity, and independence in line with their potential and developmental stages. Economics learning in Phase E of Grade X senior high school serves as a fundamental basis for understanding core economic concepts. This study developed and evaluated the EcoLearn application, an adaptive and interactive m-learning–based medium, using the ADDIE model. A quasi-experimental design with nonequivalent control groups was implemented at SMAN 4 Sidoarjo (35 students per class) and SMAN 2 Sidoarjo (40 students per class). Expert validation confirmed high feasibility (content 87.82%, media 95.71%, language 95.38%). The experimental classes showed significant improvement in conceptual understanding compared to the control classes, with N-Gain scores of 0.7775 and 0.7592 (high category). Student responses were highly positive (92.14% and 93.13%), highlighting ease of use and increased motivation, particularly for inclusive students. The findings demonstrate that EcoLearn is effective, feasible, and impactful in strengthening differentiated learning, while also supporting inclusive education for students with mild learning difficulties such as slow learners and physically disabled students.